2020
DOI: 10.1016/j.jnnfm.2020.104298
|View full text |Cite
|
Sign up to set email alerts
|

On the shear thinning of non-Brownian suspensions: Friction or adhesion?

Abstract: Shear thinning is fundamental to a broad range of particle suspensions, both in nature and in industrial applications. Yet the mechanisms governing it remain unclear. In particular, the distinct, and often competing, roles of the interparticle, particle-fluid interactions and the particle surface morphology need clarity. By using non-Brownian silica particles with different morphology, surface functional groups and suspending media, here we reveal two different shear thinning mechanisms, controlled either by f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 59 publications
7
20
0
Order By: Relevance
“…In our previous work [ 12 ], we showed that the strong shear thinning behaviour of the PS52 suspensions, as opposed to that of GS2, can be attributed to the surface asperities being elastically deformed due to the frictional contacts between the former particles. According to a theory introduced by Chatté et al [ 36 ] and Lobry et al [ 28 ], this leads to a decrease in the microscopic friction coefficient and shear thinning.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…In our previous work [ 12 ], we showed that the strong shear thinning behaviour of the PS52 suspensions, as opposed to that of GS2, can be attributed to the surface asperities being elastically deformed due to the frictional contacts between the former particles. According to a theory introduced by Chatté et al [ 36 ] and Lobry et al [ 28 ], this leads to a decrease in the microscopic friction coefficient and shear thinning.…”
Section: Resultsmentioning
confidence: 97%
“…Unlike the glass sphere suspensions, the PS52 particles exhibit the onset of shear thinning response at much lower particle volume fractions ( ), attributed to a frictional shear thinning mechanism [ 12 ], based on the elastic deformation of the surface asperities during particle contact, resulting in a decrease in the microscopic friction coefficient with shear rate [ 9 , 28 , 36 ]. Thus, particle surface asperities seem to compete with the interparticle interaction screening induced by the glycerol layer, and in the case of PS52 particles, the surface asperities seem able to penetrate the solvation layer inducing particle contacts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations